Role społeczne odgrywane przez kobietę na przykładzie wybranych czasopism kobiecych - Olko, Patrycja; Filip, Grażyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The image of a woman nowadays is quite schematic. A special part in the creation of both her appearance and the patterns of her behavior play magazines for women. They impose on women how to live in order to be trendy. Nowadays, the woman plays multiple roles in society. They include those defined by gender, stereotypes or tradition, as well as completely new, often controversial roles. On the one hand, the woman is encouraged to be a good mother, even the so- called Mother- Pole and a perfect hostess, on the other hand, however, she is being persuaded to break the traditional way of thinking. In addition to traditional roles, which are known since childhood, the reader should also familiarize herself closer and more deeply with the other ones, proposed by the magazines. Social roles, highlighted in magazines targeted at today’s readers, are presented in the article “Social roles played by a woman on the example of selected women’s magazines”. They were analyzed on the basis of the collected material and presented from the most important and most desirable. Eight social roles were distinguished, and these are: cook, mother, wife and lover, perfect housewife, interior designer, lawyer, renovation and construction worker, enterprising economist.
Tekst jest debiutem naukowym Patrycji Olko. Artykuł stanowi fragment pracy magisterskiej obronionej w 2015 r. na Uniwersytecie Rzeszowskim pod kierunkiem dr hab. prof. UR Grażyny Filip.